The Heart and the Head: On Choosing Experiences Intuitively and Possessions Deliberatively. (11th November 2016) - Gallo, Iñigo; Sood, Sanjay; Mann, Thomas C.; Gilovich, Thomas
Abstract: An enduring question in the field of judgment and decision making is when people are likely to choose on the basis of intuition and when they are likely to pursue a more deliberative decision strategy. Here, we attempt to shed light on that question by examining whether people tend to weight intuition more heavily when making experiential purchases, and to weight deliberation more heavily when making material purchases. Results from seven studies indicate that they do. In Study 1 (and a replication), participants expressed an explicit preference for choosing experiential purchases intuitively and material purchases analytically. In Study 2 (and a replication), participants anticipated experiencing more regret after going against reason for material purchases and going against intuition for experiential purchases. Participants in Study 3 who were asked to think about an experiential purchase wanted to see the relevant information presented by alternative, which facilitates intuitive/holistic processing, more than did those who were asked to consider a material purchase. In two additional studies, participants who were induced to think intuitively chose experiential purchases more often (Study 4) and reported a higher willingness to pay for them (Study 5) compared with participants induced to think analytically. Copyright © 2016 John Wiley & Sons, Ltd.